Glaucoma: Biological Trabecular and Neuroretinal Pathology with Perspectives of Therapy Innovation and Preventive Diagnosis - Nuzzi, Raffaele; Tridico, Federico (Frontiers in Neuroscience, 2017)
Glaucoma is a common degenerative disease affecting retinal ganglion cells (RGC) and optic nerve axons, with progressive and chronic course. It is one of the most important reasons of social blindness in industrialized countries. Glaucoma can lead to the development of irreversible visual field loss, if not treated. Diagnosis may be difficult due to lack of symptoms in early stages of disease. In many cases, when patients arrive at clinical evaluation, a severe neuronal damage may have already occurred. In recent years, newer perspective in glaucoma treatment have emerged. The current research is focusing on finding newer drugs and associations or better delivery systems in order to improve the pharmacological treatment and patient compliance. Moreover, the application of various stem cell types with restorative and neuroprotective intent may be found appealing (intravitreal autologous cellular therapy). Advances are made also in terms of parasurgical treatment, characterized by various laser types and techniques. Moreover, recent research has led to the development of central and peripheral retinal rehabilitation (featuring residing cells reactivation and replacement of defective elements), as well as innovations in diagnosis through more specific and refined methods and inexpensive tests.